On the impact of mass difference between the pions (π±-π0) and the nucleons (n-p) on the charge independence breaking of nuclear forces - V. A. Babenko; N. M. Petrov (Ядерна фізика та енергетика)
Charge dependence of the pion-nucleon coupling constants and the 1S0-state low-energy nucleon-nucleon scattering parameters are studied on the basis of the Yukawa meson theory. The charge independence breaking effect in the pion-nucleon coupling constants is entirely explained by the mass difference between the charged and the neutral pions and by the mass difference between the proton and the neutron. Using of well-known pseudovector pion-nucleon coupling constant f 2ppπ0=0.0749(7), which characterize the proton-proton nuclear interaction, we calculate the charged f 2c=0.0802(7) and the neutral f 20=0.0750(7) pion-nucleon coupling constants, and also the pion-nucleon coupling constant f 2nnπ0=0.0751(7), which characterize the neutron-neutron nuclear interaction. With the help of the obtained coupling constants, we also calculate values of the low-energy np- and nn-scattering parameters, which appear to be in good agreement with the experiment.